Socially active school as an actor of community social work in Ukraine - Євдокимова, І. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article is devoted to the analysis of socially active schools as subjects of social work under decentralization in Ukraine. It is noted that in the context of the reform of local self-government and decentralization in Ukraine, a contradiction is formed between the need to create an accessible system of social support for the population and the possible inability of many united territorial communities to form it. Therefore, united territorial communities should use all available resources and opportunities to ensure the effective provision of social support to the population. One of such resources is school, in particular, its special model, which is called “socially active school”. The socially active school is an educational institution in which considerable attention is paid to building partnerships between the school and community. The model of a socially active school as a center for the development of a local community includes the following areas of activity: democratization, volunteering, and school-community partnerships. Each of these areas involves the use of various tools by a socially active school. Democratization involves the introduction of some democratic procedures in the school: democratization of lessons, creation of effective bodies of school self-government. Volunteering is associated with volunteer actions that becoming an integral part of the school. The partnership between the school and the community is seen as the establishment and development of mutually beneficial relations between the school and the local community for joint problem solving. The main tools in this area of activity are providing of various services, including social, for residents; organizing joint events; developing and implementing social programs and projects, educational activities, etc. In the process of implementing such activities the school gradually becomes a resource center of the local community and turns into an important subject of social work. The article discusses the history of socially active schools, the main directions and instruments of their activity, concludes that socially active schools could play the significant role in community social work.